MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING DI KELAS X SMA NEGERI 6 CIMAHI - Alifa Azmil Fauziah; Citra Megiana Pertiwi (IKIP Siliwangi, 2022)
This research is based on the ability of mathematical understanding (KPM) of students in class X IPS 3 SMAN 6 Cimahi is still low. From the results of the evaluation of the KPM indicator test on the Three Variable Linear Equation System (SPLTV) material, only 13 students achieved the minimum completeness criteria of 36 students. The research carried out is in the form of classroom action research to improve the learning process in order to improve student learning outcomes in SPLTV material through discovery learning models. This research has been carried out in class X IPS 3 SMAN 6 Cimahi, totaling 36 students. The research instruments were lesson plans and worksheets, and the data collection instruments used were observation sheets and KPM evaluation tools. The observation sheet will be analyzed descriptive qualitatively, and the KPM data will be analyzed quantitatively. Based on the results of the evaluation that has been carried out by the authors, it is obtained: in cycle 1 the student KPM level is 42.78%, in cycle 2 it is 60.55%, and in cycle 3 it is 81.66%. So it can be concluded that learning with the discovery learning model can improve students' KPM.